Promosi dan Brand Image Serta Dampaknya Terhadap Minat Beli Fashion di Situs E-Commerce Tokopedia - Khofia, Irham; Dirgantari, Puspo Dewi; Munawar, Meki (Eqien - Jurnal Ekonomi dan Bisnis, 2024)
This research was conducted to find out what factors influence buying interest. In this research, promotion and brand image are used as dependent variables. Primary data collection using a non-probability sampling technique, namely a sampling technique that does not provide the same opportunity/opportunity for every member of the population to be a sample. The data analysis method used in this research is multiple linear regression with the help of SPSS 22 software. And the overall dependent variable has a stimulant effect on Buying Interest with a calculated F value of 171,596 with a significance level of 0.000 <0.5. And the value of R square shows the results of 0.785, which means that the entire dependent variable has a simultaneous effect of 78.5%.